On Courts Herding Cats: Contending with the “Written Description” Requirement (and Other Unruly Patent Disclosure Doctrines) - Mark D. Janis (Washington University Journal of Law & Policy, 2000)
This Essay explores the problem of incoherence among modern disclosure doctrines.
Keywords: Discovery (Law); Patent law